PENAMBAHAN TEPUNG PORANG PADA PEMBUATAN MI DENGAN SUBSTITUSI TEPUNG MOCAF (Modified cassava FLOUR) [Addition of Porang Flour in Noodle as Mocaf Substitution (Modified cassava Flour)] - Anni Faridah; Simon Bambang Widjanarko (Jurnal Teknologi dan Industri Pangan, 2014)
PENAMBAHAN TEPUNG PORANG PADA PEMBUATAN MI DENGAN SUBSTITUSI TEPUNG MOCAF (Modified cassava FLOUR)[Addition of Porang Flour in Noodle as Mocaf Substitution (Modified cassava Flour)]Anni Faridah1)* dan Simon Bambang Widjanarko2) 1) Fakultas Teknik, Univeritas Negeri Padang, Padang2) Fakultas Teknologi Pertanian, Universitas Brawijaya, Malang Diterima 16 Januari 2014 / Disetujui 25 Juni 2014ABSTRACT  Noodle is one of the staple foods that are widely consumed and preferred by the Asian. However, wet noodles with modified cassava flour (mocaf) substitution resulted in lower quality compared to 100% wheat noodle. Addition of a certain amount of konjac glucomannan (Amorphophallus oncophyllus flour) to wet noodle is strongly recommended due to the fact that the food additive has a health benefit. Porang or konjac flour, which was used in the research, has soluble fiber properties, low calorie content, and highly viscous. It forms a heat stable gel with a mild alkali, interacts with starch, and has a synergistic interaction with kappa carrageenan. In this research, konjac flour was added to study the optimum combination between konjac and water. As much as 2, 4 and 6% (w/w) of konjac flour were combined with 35, 40, 45% (v/w) of water. The results showed that treatments with combinations of konjac flour and water were significantly contributing to characteristics of cooking time, cooking loss, color brightness index, tensile strength, swelling volume and water absorption. The best treatment was at a combination of 4% konjac (w/w) and 35% water (v/w). The best porang noodles have the characteristics of cooking time at 2.13 minutes, cooking loss of 35%, tensile strength of 0.14 N, water absorption of 201.58%, color brightness index of 51.41, swelling volume of 103.63%, moisture content of 31.77%, protein content of 5.87%, fat content of 2.13%, ash content of 0.85% and crude dietary fiber of 4.58%.